The Effect of Economy Bitcoin on Money Supply with the Growth of Bitcoin Volatility as an Intervening Variable - Nindya Dera Permatasari; Muhammad Azhari (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
Bitcoin is one of many Cryptocurrency that was intended to ease the peer-to-peer payment method where it’s users can directly interact without an intermediary. The value of Bitcoin is determined by the demand and offer without the interference of other parties so it tends to fluctuate. The demand for Bitcoin is increasing from the service provider of Cryptocurrency in the form of digital asset exchange, especially in Malaysia. This research was done to find out if there’s an effect from the Bitcoin economy to the money supply in Malaysia. The time-series data in the form of the provider of virtual money in Malaysia, data on the growth of Bitcoin volatility, and the data of the money supply in Malaysia (M1). The data is taken at the end of each month during the study period from January 2016 to June 2019. Purposely to answer the question of this research the data is analyzed using the classic assumption, the simple linear regression test, and t-test. The result from the data processing is shown Bitcoin economy has a significant effect on the money supply in Malaysia.